Turkish Adaptation of Multidimensional Nursing Generation Scale - Gamze Kutlu Türedi; Serap Altuntaş (Association of Nurse Managers, 2022)
Aim: The study was conducted to adapt the Multidimensional Nursing Generations Scale to Turkish. Method: The study was carried out in methodological design and with 447 nurses in five hospitals in Bursa. The original 'Personal Information Form' and 'Multidimensional Nursing Generations Scale' was used to collect the data. Ethical approval and institutional approval were obtained for the study. In the study, the language equivalence and scope equivalence of the scale were ensured and a pilot application was made, and descriptive statistics and psychometric tests were used in the evaluation of the obtained data. Results: The scale, which was adapted after the evaluation of the data, showed a structure with 36 items, explaining 52% of the total variance, and a four-factor structure with an eigenvalue above 1.00. It was determined that item-total score correlation values were between.33 and.58, factor loads were between.33 and.86, the level of discrimination and concordance were high, and Cronbach's alpha values ranged between.76 and.92. Conclusion: The results of the study show that the scale adapted to Turkish culture is a valid and reliable scale that can be used to determine generational differences among nurses.